PENERAPAN PEMBELAJARAN BERBASIS KOMPUTER OLEH GURU DI SMP NEGERI SEKECAMATAN BATURAJA BARAT - Anggraeni Agustin Muris (Jurnal Ilmiah Matrik, 2017)
Effective and efficient learning today is so well known that it is called computer-based learning. Learning activities are conducted more thoroughly so that teachers can train students on an ongoing basis until the students can achieve learning to completion. The purpose of this research is to know the Application of Computer Based Learning by Teachers at SMP Negeri Sekecamatan Baturaja Barat. The type of this research is quantitative is descriptive. Population and sample in this research is all teacher who do study at SMP Negeri Sekecamatan Baturaja Barat. Data collection tool in this study using questionnaires and documentation and data analysis techniques used is to use the formula percentage. The results of research on the application of computer-based learning as a whole is very good. This is evidenced by the questionnaire that has been filled by the respondents